A kind of paradise - Tan, Amy Rebecca (Harper, 2019)
Thirteen-year-old Jamie Bunn broke her school's honor code at the end of the school year by making a huge, embarrassing mistake. Now she has to spend her summer vacation volunteering at the local library as punishment. But soon, Jamie starts to make friends with the employees and regular patrons of the library and enjoys the work. As the summer progresses and the future of the library is threatened, Jamie learns about the power of forgiveness and community.